Association of childhood maltreatment with internalising and externalising disorders in trauma-exposed adolescents - Leigh L. van den Heuvel; Milo Koning; Jani Nöthling; Soraya Seedat (South African Journal of Psychiatry, 2018)
Introduction: South African adolescents experience high levels of trauma, including various types of childhood maltreatment. Different types of maltreatment often co-occur. Previous research suggests that childhood maltreatment provokes a latent liability to internalising and externalising dimensions of psychopathology. Our objective was to examine the effects of childhood maltreatment on internalising and externalising disorders in trauma-exposed adolescents and to assess the mediating effect of post-traumatic stress disorder (PTSD) on these associations.